2011
DOI: 10.14429/djlit.31.2.865
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Academic Research Output during 1996-2009: A Case Study of PEC University of Technology, Chandigarh

Abstract: The study investigates the contribution and impact of research output of PEC University of Technology as reflected in its publications covered in Scopus international multidisciplinary database. The study describes the broad characteristics of research publications of PEC during 1996-2009, its growth, format, media of communication, national and international collaboration profile and overall citation impact, distribution of research output and impact under broad subjects and under different subject department… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Vasishta 6 undertook a study, based on data extracted from scopus, of the 177 papers of PEC (Punjab Engineering College) University of Technology, Chandigarh published between 1996 and 2009 to examine the research productivity, publication trend, collaboration trend, etc. The study reported that though there was steady growth in research publications, there was a need to improve the publication output substantially when comparison was made to the publication output of other engineering colleges.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Vasishta 6 undertook a study, based on data extracted from scopus, of the 177 papers of PEC (Punjab Engineering College) University of Technology, Chandigarh published between 1996 and 2009 to examine the research productivity, publication trend, collaboration trend, etc. The study reported that though there was steady growth in research publications, there was a need to improve the publication output substantially when comparison was made to the publication output of other engineering colleges.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that Chemistry is the most favoured research areas followed by Physics, Astronomy, Plant science etc. The degree of collaboration is 0.99 (nearly equals to 1) that means there is few/small contributions by single authors and Indian Institute of Technology were the most prolific institution Downloaded by [New York University] [7] examined the contribution and impact of research output of PEC University of Technology. The research output of the PEC was increased with average annual growth rate of 131.85 per cent during 1996 to 2009.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Vasishta 4 examined the contribution and impact of research output of PEC University of Technology as reflected in its publications covered in Scopus international multidisciplinary database. The study described the broad characteristics of research publications of PEC during 1996-2009, its growth, format, media of communication, national and international collaboration profile and overall citation impact, distribution of research output and impact under broad subjects and under different subject departments, most productive authors, and highly cited papers.…”
Section: Review Of Literaturementioning
confidence: 99%